2020
DOI: 10.1021/acsenergylett.0c02081
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Observation of Solid Electrolyte Interphase Bilayer Inversion on Silicon Oxide

Abstract: Silicon has been investigated in recent years as an alloying anode material to enhance gravimetric energy density in lithium-ion batteries. While recent developments have suggested that silicon oxides exhibit improved cycling stability over pure Si, the origin of the improved cycling performance is still poorly understood. The initial solid electrolyte interphase (SEI) formation mechanisms on Si wafers with both native oxide and chemically etched thermal oxide coatings are investigated structurally, chemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 36 publications
(88 reference statements)
2
23
0
Order By: Relevance
“…Moreover, organic carbonate species are regarded as the key components in the SEI, which is in conflict with the conclusion in the recent literature. [ 63 ]…”
Section: The Fundamental Understanding Of Seimentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, organic carbonate species are regarded as the key components in the SEI, which is in conflict with the conclusion in the recent literature. [ 63 ]…”
Section: The Fundamental Understanding Of Seimentioning
confidence: 99%
“…LiPF 6 was selected as an F‐containing anion Li salt for the electrolyte solution, the mixed solvent does not contain F. In addition, very recently, Stetson et al. [ 63 ] proposed a new insight into SEI on Si anode and Si with oxide film anode. For an Si anode with the treatment of HF‐etched SiO 2 , after the formation of SEI by an electrochemical reaction, the inner layer displays an inverted bilayer structure, with organic‐rich composition SEI presenting at the Si anode interface and inorganic composition SEI in the outer SEI, which is quite different from an Si anode with a layer of native film (Figure 6d).…”
Section: The Fundamental Understanding Of Seimentioning
confidence: 99%
“…The special structure is conducive to forming a stable solid electrolyte interphase (SEI) layer and reducing volume changes of active materials. [29][30][31][32] Carbon coating can also effectively hinder the formation of silicon crystals and reduce the polarization resistance of the electrode, thereby improving the conductivity and electrical performance of it. [33][34][35] This paper also studied the ratio of glucose hydrothermal coating.…”
Section: Introductionmentioning
confidence: 99%
“…[23] By analyzing the electrochemical curves and interface/surface compositions, it has been revealed that the partially reversible formation/dissolution of the growing SEI results in the capacity increase of Sn-based anodes as cycled with charge potential higher than 2.5 V. [27] For a conversion MnO anode, Zhang et al [20] investigated the importance of SEI homogeneity in terms of both morphological and mechanical properties on the cycling performance and safety of LIBs. Recent experimental work by Stetson et al [19] presented distinct initial SEI formation mechanisms that could contribute to the improved cycling life in conversion-alloying SiO x anode compared to alloying Si anode. Besides, great efforts have been made to modify the SEI films by adding additives in electrolyte or establishing an artificial electrode/electrolyte interface, desiring to obtain elastic and uniform SEI film.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies have established a fundamental understanding of the relationship between SEI characteristics and performance of anodes involving in conversion or alloying reactions. [19,20,28] The amorphous compound containing carbon…”
mentioning
confidence: 99%